Ligusticum chuanxiong Hort as a medicinal and edible plant foods: Antioxidant, anti-aging and neuroprotective properties in Caenorhabditis elegans - Qin, Yihan; Chen, Fangfang; Tang, Zizhong; Ren, Hongjiao; Wang, Qing; Shen, Nayu; Lin, Wenjie; Xiao, Yirong; Yuan, Ming; Chen, Hui; Bu, Tongliang; Li, Qingfeng; et al. (Frontiers in Pharmacology, 2022)
Ligusticum chuanxiong Hort. (CX) is a medicinal and edible plant including a variety of active substances, which may be a potential resource for the treatment of related diseases. In addition, since the biomass of the non-medicinal parts of CX is huge, discarding them will cause a waste of resources. To expand the medicinal uses of CX, this study aims to explore the antioxidant, anti-aging and neuroprotective effects of the Ligusticum chuanxiong leaves (CXL) and rhizome (CXR) extracts (CXs). We first characterize CXs phytochemical spectrum by LC-MS as well as antioxidant capacity. Acute toxicity, anti-oxidative stress capacity, lifespan and healthspan was evaluated in C elegans N2. Neuroprotective effect was evaluated in vitro and in vivo (C elegans CL4176 and CL2355). Moreover, the possible mechanism of CXs effects was explored through qPCR, antioxidant enzyme activity, ROS accumulation analysis and a single gene deletion worms. In this study, we detected 74 and 78 compounds from CXR and CXL, respectively, including phthalides, alkaloids, organic acids, terpenes, polyphenols and others. Furthermore, we found that CXs not only protect against oxidative stress, but also prolong the lifespan, alleviate lipofuscin, MDA and ROS accumulation, and improve movement level, antioxidant enzyme activity in C elegans N2. However, only CXR reduced the β-amyloid peptide (Aβ)-induced paralysis phenotype in CL4176s and alleviated chemosensory behavior dysfunction in CL2355s. In addition, CXR treatment reduced the production of Aβ and ROS, enhanced SOD activity in CL4176s. The possible mechanism of anti-aging of CXL and CXR is to promote the expression of related antioxidant pathway genes, increase the activity of antioxidant enzymes, and reduce the accumulation of ROS, which is dependent on DAF-16 and HSF-1(only in CXR). CXR was able to activate antioxidase-related (sod-3 and sod-5) and heat shock protein genes (hsp-16.1 and hsp-70) expression, consequently ameliorating proteotoxicity related to Aβ aggregation, although it is not known whether these effects were achieved directly or indirectly. In summary, these findings demonstrate the antioxidant, anti-aging and neuroprotective (only in CXR) activities of the CXs, which provide an important pharmacological basis for developing functional foods and drugs to relieve the symptoms of aging and AD.